A STUDY OF SEVERITY OF STROKE AND HOMOCYSTEINE LEVEL IN SOUTHERN PART OF RAJASTHAN, INDIA - MEHTA, VINOD KUMAR; BASU, ABHIJIT; H PATHAK, PRAHARSH; JAIN, AYUSHI; SHARMA, NEHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Till date, a very few prospective studies have examined the association between serum homocysteine levels and the risk of stroke and stroke subtypes in Indian populations. Methods: A prospective, case - control study of Indian subjects 10–90 years of age was conducted using frozen serum samples from 103 participants in cardiovascular risk surveys collected from December 2017 to November 2018. By the end of 103, we identified 55 incidents of severe strokes, one control subject per case was selected by matching for sex, age, community, year of serum storage, and fasting status. Serum total homocysteine levels were measured by Cobas c-311. Results: Compared with control subjects, total (n_206), hemorrhagic (n_106), and ischemic (n_87) strokes had higher geometric mean values of total homocysteine and higher proportions of homocysteine −25.0 μ mol/L. Homocysteine was estimated after adjustment for body mass index, smoking, alcohol intake, hypertension, and other cardiovascular risk factors. The excess risk of total and ischemic strokes did not vary significantly according to sex, age, smoking status, or hypertensive status. Conclusion: High total homocysteine concentrations were associated with the increased risk of total stroke, more specifically ischemic stroke) Capsuloganglionic and frontoparietal infarct (8 each)., among Indian men and women.